SIFAT MEKANIK DAN SERAPAN AIR PLASTIK KOMPOSIT KITOSAN-LEMPUNG - , MURNIATY; , Dr.Indriana Kartini, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Preparation of chitosan and chitosan-clay plastic using redeacetylated chitosan and natural clays has been done. The plastics were prepared by drying the solution of chitosan powders in acetic acid solution (1%, v/v) at 65 Â°C for 7h. The structural and mechanical properties were characterized using infrared spectrophotometer, X-ray diffraction (XRD), and universal testing machine. The water sorption properties of the plastics were tested using GAB (Guggenheim Anderson de Boer) sorption isotherms method and water vapor transmission rate (WVTR), and water vapor permeability (WVP) method at 29 ï C and 62% RH (Relative Humidity). Thermogravimetry/ differential thermal analysis (TG/DTA) was performed to analyze the thermal properties. Infrared spectra indicated that the amine to acetyl mole ratio of the chitosan powder increased as the increase of deacetylation frequency. XRD data showed that chitosan powder resulted from three times deacetylation process has higher crystallinity index (64.8%) compared to the untreated parent chitosan (34.1%) indicating the formation of more ordered structure. The crystalline structure of chitosan powder affected the mechanical and water sorption properties of chitosan plastics. Tensile strength of chitosan plastic increased (42 MPa) and the elongation-at-break decreased (6.20 %) as the crystallinity increased. Water sorption values of WVP and WVTR decreased successively as the number of deacetylation increased. Chitosan plastic resulted from more crystalline structure of chitosan powder has the lowest water sorption properties (WVTR of 27 g/m2 day and WVP of 2.67 x 10-9 g m/m2 day Pa). In chitosan matrix, clay was found both in intercalated and exfoliated structures as indicated by the XRD patterns. Tensile strength of chitosan plastic (62.62 MPa) increased and the elongation-at-break (5.50 %) decreased after clay addition. Chitosan-clay composite plastic showed smaller water sorption properties (WVTR = 25.2 g/m2.day and WVP = 2.49 x 10-9 g.m/m2.day.Pa) leading to better water vapor permeability properties needed for food packaging than that of chitosan plastic